Evaluasi Potensi Jalur Trekking Hutan Pendidikan USU, Taman Hutan Raya Bukit Barisan, Kabupaten Karo (Evaluation of Potential Tracking Rute at Educational Forest of USU, Bukit Barisan Grand Forest Park, Regency of Karo) - Devita Saragih; Pindi Patana; Rahmawaty Rahmawaty (Peronema Forestry Science Journal, 2013)
Educational Forest of USU has many interesting objects, unfortunately it has not had development activity yet that can support Educational Forest of USU as a ecotourism destination. Therefore, a research about potential evaluation of ecotourism had been conducted at track of Educational Forest of USU in July – August 2012. This research aimed to evaluate the potential use of track of Educational Forest of USU for ecotourism activities. The research was conducted by using force field analysis method to decide supporting factors and obstacle factors that influenced at Educational Forest of USU. Usu has many ecotourism potencies such as the beauty of nature, flora and fauna. Educational Forest of USU has excellent potential to be developed as a tourist area and needs a great strategy from the administrator to be an interesting ecotourism region. Key Words: Tracking Rute, Educational Forest of USU, Bukit Barisan Grand Forest Park, Ecotourism